Hubungan Antara Tipe Kepribadian Dengan Orentasi Religiusitas - Suminta, Rini Risnawati (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2016)
The aim of the present study was to determine the relationship between big five personality and religious orientation. The subjects of this study were students of Islamic psychology program, Department of Ushuluddin, State College of Islamic Religion Kediri. Samples (N=99) were collected through a simple random sampling, and completed a questionnaire in the form of a scale. The instrument in this research had been aplided by the big five personality scale and religious orientation scala. The analyzis for this research using the Product Moment Analizing for Correlation between the variables with SPSS program. The results of the study showed that there was a positive significant relationship between extraversion, openness to experience, agreeableness and intrinsic religious orientation and in contrast there was a negative significant relationship between neuroticism and conscientiousness and intrinsic religious orientation.